Single sitting endourological management of retained ureteral stents at Groote Schuur Hospital: A 3-year retrospective study - Ombuki, Winstar (Division of General Surgery, 2024)
Double J stents have become essential components in endourological and open urological procedures. The removal ofseverely encrusted and retained ureteralstents poses a management challenge for urologists as multiple procedures are often required to remove them. Objectives: Main Objective: To determine the proportion of patients with retained stents who can be rendered stent free with single-sitting endourological management Secondary Objectives: To describe the number of procedures required to render patients with retained stents stent and stone free. To describe the demography and clinical variables of patients with retained ureteral stents at Groote Schuur Hospital Materials and Objectives: A retrospective study was conducted between 1st February 2018 and 31st January 2022. All 30 patients that met inclusion criteria with retained and encrusted patients were reviewed. All patients were initially evaluated with radiographic imaging for assessment of stone burden. Treatment decisions were based on the FECAL classification of retained stents. Multimodal endourological procedures were used to achieve the stents and render the patient stone free. Results: The average age of the participants was 39.4 years while the male participants were the most common, 66% (n= 19). A total of 47 Urological procedures were performed to render all 30 patients' stent and stone free. The average duration of indwelling time was 20.35 months and a range of 66 months with a minimum of 4 months and a maximum of 70 months. The main indication for stent placement was stone obstruction ( 55.56%) 41% (n= 12) of patients had PCNL while 48% (n= 14) patients received ureteroscopy and laser lithotripsy. The most common FECAL classification was IV at 59% (n= 17). The most common side affected by stent encrustation was the right (55.56%). Conclusion: The endoscopic combined approached is safe and feasible technique that allows removal of retained and encrusted stents in a single procedure.